Alocação de fotoassimilados marcados e relação fonte-dreno em figueiras cv. Roxo de Valinhos. 1. Relação fonte e dreno - Silva, Andréa C. da; Leonel, Sarita [UNESP]; Souza, Adilson P. de; Vasconcellos, Marco A. da S.; Rodrigues, João Domingos [UNESP]; Ducatti, Carlos [UNESP] (Revista Brasileira de Ciencias Agrarias, 2011)
The work aimed at evaluating the photosynthates allocation using the stable carbon 13 isotope as marker, as well as evaluating the source-sink dynamics in the different organs in Ficus carica L. plants in the reproductive stage. A fig tree leaf considered adult by the photosynthetic characterization with a portable photosynthesis meter IRGA-6400 was put inside an acrylic chamber, built specifically for this experiment, and submitted to an environment with 13CO 2 enrichment for 30 minutes. After 24 hours, the studied plant parts (apical meristem, leaves, branches, stem and root system) were collected and immediately immersed in liquid nitrogen (-196°C). The samples were oven-dried (65°C, 72 hours), crushed in cryogenic mill, and further analyzed in the mass spectrometer of isotopic reason, to determine the 13C relative enrichment. Naturally, the plant presented values of relative enrichment of δ 13C -27.92‰ The plant presented concomitant vegetative growth and reproductive stage, showing preference in the 13C allocation in the meristem areas, followed by the reproductive organs, having the fibrous roots as reserve drain.
Allocation of marked photoassimilated and sourcesink dynamics in fig trees cv. Roxo de Valinhos. 1. Source and sink dynamics
Keywords: 13C-translocation; Carbohydrate reserves; Ficus carica; L.; Ficus (angiosperm)